Stability of the Glenohumeral Joint With Combined Humeral Head and Glenoid Defects: A Cadaveric Study. (April 2016) - Gottschalk, Lionel J.; Walia, Piyush; Patel, Ronak M.; Kuklis, Matthew; Jones, Morgan H.; Fening, Stephen D.; Miniaci, Anthony
Background: Shoulders with recurrent anterior instability often have combined bony defects of the humeral head and glenoid. Previous studies have looked at only isolated humeral head or glenoid defects. Purpose/Hypothesis: The aim of this study was to define the relationship of combined humeral head and glenoid defects on anterior shoulder instability. Combined bony defects will lead to increased instability compared with an isolated defect, and the "critical" size of humeral head and glenoid defects that need to be addressed to restore stability will be smaller when combined rather than isolated. Study Design: Controlled laboratory study. Methods: Eighteen shoulder specimens were tested at 60° of glenohumeral abduction and 80° of glenohumeral external rotation. Humeral head defect sizes included 6%, 19%, 31%, and 44% of the humeral head diameter. Glenoid defect sizes included 10%, 20%, and 30% of the glenoid width. Outcome measures included percentage of intact stability ratio (%ISR; the stability ratio for a given trial divided by the stability ratio in the intact state for that specimen) and percentage of intact translation (%IT; the distance to dislocation for a given trial divided by the distance to dislocation in the intact state for that specimen). Results: The decrease in %ISR reached statistical significance for humeral head defects of 44%, for glenoid defects of 30%, and for a combined 19% humeral head defect with a 20% glenoid defect (65% mean %ISR). The decrease in %IT reached statistical significance for humeral head defects ≥31%, for glenoid defects ≥20%, and for a combined 19% humeral head defect with a 10% glenoid defect (69% mean %IT). Conclusion: In shoulders with combined humeral head and glenoid defects, bony reconstruction may be indicated for humeral head defects as small as 19% of the humeral head diameter and glenoid defects as small as 10% to 20% of the glenoid width, especially if the glenoid defect produces a significant loss of glenoid concavity depth. Clinical Relevance: In shoulders with combined humeral head and glenoid defects, bony reconstruction may be indicated for defect sizes smaller than would be indicated for either defect found in isolation.